End points and assessments in esthetic dental treatment. Issue 4 (October 2015) - Ishida, Yuichi; Fujimoto, Keiko; Higaki, Nobuaki; Goto, Takaharu; Ichikawa, Tetsuo
Abstract: Purpose: There are two key considerations for successful esthetic dental treatments. This article systematically describes the two key considerations: the end points of esthetic dental treatments and assessments of esthetic outcomes, which are also important for acquiring clinical skill in esthetic dental treatments. Study selection: The end point and assessment of esthetic dental treatment were discussed through literature reviews and clinical practices. Results: Before designing a treatment plan, the end point of dental treatment should be established. The section entitled "End point of esthetic dental treatment" discusses treatments for maxillary anterior teeth and the restoration of facial profile with prostheses. The process of assessing treatment outcomes entitled "Assessments of esthetic dental treatment" discusses objective and subjective evaluation methods. Conclusions: Practitioners should reach an agreement regarding desired end points with patients through medical interviews, and continuing improvements and developments of esthetic assessments are required to raise the therapeutic level of esthetic dental treatments.